INTERNAL QUALITY ASSURANCE OF EDUCATION FUND PROJECT SCHOOLS UNDER THE OBEC IN KANCHANABURI PROVINCE - Wongpracharrat, Chanpim; Boonyapo, Somgit; Theansomjai, Sommai (Journal of MCU Phetchaburi Review, 2025)
This research aimed to examine: 1) The Implementation Results of Internal Quality Assurance in Education Fund Project Schools under the Office of the Basic Education Commission in Kanchanaburi Province , and 2) policy recommendations for internal quality assurance practices in schools under the Education Fund Project affiliated with the Office of the Basic Education Commission in Kanchanaburi Province. The research employed a mixed-method approach, using both questionnaires and interviews. The target group consisted of 27 schools participating in the Equitable Education Fund Project. The key informants included school principals, chairpersons of the Basic Education Committees, and personnel responsible for internal quality assurance. A totaling 81 individuals. The data were analyzed using frequency, percentage, mean, standard deviation, and content analysis. The research findings revealed that: (1) the overall implementation of internal quality assurance in schools under the Education Fund Project affiliated with the Office of the Basic Education Commission in Kanchanaburi Province was rated at the highest level. The aspects, ranked from highest to lowest, were as follows: 1) implementation based on the educational development plan, 2) preparation of self-assessment reports, 3) monitoring of implementation to ensure quality according to educational standards, 4) development of educational plans aimed at achieving quality in accordance with educational standards, 5) establishment of school-based educational standards, and 6) internal evaluation and quality inspection. (2) Guidelines for the implementation of internal quality assurance in these schools included: surveying the needs of parents and communities, analyzing and setting educational standards, collaboratively developing educational plans with stakeholder involvement, providing a conducive school environment, clarifying the results of implementation monitoring, using data to improve operations, analyzing evaluation results, applying the results to promote continuous quality development, and utilizing recommendations from internal quality assessments for further improvement.